+0  
 
-1
124
1
avatar+761 

Help.

NotSoSmart  Apr 3, 2017
Sort: 

1+0 Answers

 #1
avatar+77125 
+2

8.  (x + 6)^2 + (y - 7)^2  = 81

 

9.  The radius  = sqrt [ (-6 - 0)^2 + ( -8 - 0)^2 ] =  sqrt (100) = 10

 

So...the equation is   (x + 6)^2 + (y + 8)^2  = 100

 

 

10.  We have

 

( 3 - h)^2 + ( -1 - 7)^2  = 100  simplify

 

3^2 - 6h  + h^2 + 64  = 100

 

h^2 - 6h + 73  = 100

 

h^2 - 6h - 27  = 0     factor 

 

(h - 9) ( h + 3)  = 0

 

Setting each factor to 0  and solving for h  we have that  h = 9 or h = -3

 

 

cool cool cool

CPhill  Apr 3, 2017

15 Online Users

avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details